Three dimensional mapping of forest canopy equivalent water thickness using dual-wavelength terrestrial laser scanning - Elsherif, Ahmed; Gaulton, Rachel; Shenkin, Alexander; Malhi, Yadvinder; Mills, Jon (Agricultural and forest meteorology, 2019)
•Dual-wavelength TLS reflectance data is highly correlated to leaf EWT.•3D estimates of forest canopy EWT were generated with low errors.•Leaves in upper canopy had higher water content than leaves in bottom canopy.•There was a gradual transition between sun and shade leaves in forest canopy. Globally, forests are being subjected to numerous threats, including climate change, wildfires, and insect and disease outbreaks, among others. Satellite optical remote sensing data have been widely utilized in early detection of tree and forest stress by estimating water status metrics such as the leaf Equivalent Water Thickness (EWT). This estimate, however, is affected by soil characteristics and understory vegetation and often ignores the effects of the fine-scale heterogeneity of canopy structure and leaf water content. Such effects can be better understood by studying the EWT distribution in three dimensions. In this study, Terrestrial Laser Scanning (TLS) intensity data from the commercially-available Leica P20 and P40 instruments (808 nm and 1550 nm respectively) were combined in a Normalized Difference Index (NDI). NDI was used to map EWT of 12 trees in three dimensions from floor to canopy in a mixed broadleaf forest plot (Wytham Woods, UK). The average error in EWT estimates across three species was less than 8%. The three dimensional point clouds revealed that, in this snapshot, EWT changes vertically, usually increasing towards canopy top. The proposed method has the potential to provide predawn EWT measurements, is independent of solar illumination, and can lead to a better understanding of the factors affecting satellite estimation of EWT.